2019
DOI: 10.1016/j.isci.2019.09.014
|View full text |Cite
|
Sign up to set email alerts
|

The Ancestral Environment Shapes Antiviral CD8+ T cell Responses across Generations

Abstract: SummaryRecent studies have linked health fates of children to environmental exposures of their great grandparents. However, few studies have considered whether ancestral exposures influence immune function across generations. Here, we report transgenerational inheritance of altered T cell responses resulting from maternal (F0) exposure to the aryl hydrocarbon receptor ligand 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD). Since F0 exposure to TCDD has been linked to transgenerational transmission of reproductive p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 88 publications
(129 reference statements)
0
15
0
Order By: Relevance
“…Unexpectedly, localization of macrophages to ilea of F2P TCDD and F2M TCDD pups was highly variable and appeared to be independent of diet as well as disease state (Figure 4). Several studies have reported multigenerational and transgenerational alterations in immune system development as a consequence of developmental or ancestral TCDD exposure (Post et al, 2019; Vorderstrasse, Cundiff, & Lawrence, 2004). Thus, the variable macrophage response of our F2P TCDD and F2M TCDD pups may reflect similar immune impairments due to their parental TCDD exposure.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Unexpectedly, localization of macrophages to ilea of F2P TCDD and F2M TCDD pups was highly variable and appeared to be independent of diet as well as disease state (Figure 4). Several studies have reported multigenerational and transgenerational alterations in immune system development as a consequence of developmental or ancestral TCDD exposure (Post et al, 2019; Vorderstrasse, Cundiff, & Lawrence, 2004). Thus, the variable macrophage response of our F2P TCDD and F2M TCDD pups may reflect similar immune impairments due to their parental TCDD exposure.…”
Section: Resultsmentioning
confidence: 99%
“…TCDD is a ubiquitous environmental toxicant and multiple studies have found that in utero exposure negatively impacts immune system development (Lawrence & Vorderstrasse, 2013). For example, Post et al (2019) reported adult mice with a direct or ancestral history of TCDD exposure exhibited an impaired ability to clear influenza infection while Peltier et al reported similarly exposed mice exhibit an inflammatory phenotype during pregnancy (Peltier et al, 2013). Our previous studies demonstrated that adult male and female F1 TCDD animals consistently demonstrate a heightened inflammatory response to either viral or bacterial challenges (Ding et al, 2011; Ding et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To detect effector proteins, cells were incubated in the presence of recombinant mouse interleukin-2 (IL-2; R&D Systems) and brefeldin A (Sigma-Aldrich) for 1 h at 37°C prior to CD16/32 mAb block or extracellular antibody staining. Anti-CD107a [LAMP-1 (lysosomal-associated membrane protein 1)] was added, and the cells were incubated for an additional 4 h at 37°C prior to extracellular staining ( Post et al. 2019 ).…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, environmental pollutants can increase susceptibility to non-communicable diseases (NCDs) and determine a significant decline in body's defences, possibly due to also transgenerational effects that may partly explain the worldwide disease burden consisting not only in non-communicable but also communicable diseases (dengue, yellow fever, tuberculosis, etc.) [24][25][26][27][28][29][30][31][32][33][34][35][36] . Furthermore, it shows that this is transmitted to the following generations, by reducing the defence ability toward viral pathogens 26 .…”
Section: Pollution and Susceptibility To Viral Insultsmentioning
confidence: 99%